Evaluation of ear: stem weight ratio as a criterion for selection of drought- tolerant wheat (Triticum aestivum) genotypes - RANE, JAGDISH; NAGARAJAN, SHANTHA (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1998-99 to evaluate ear; stem weight ratio as a selection criterion of drought- tolerant genotypes of wheat (Tritium aestivum L. emend. Fiori & Paol.), by subjecting genotypes slisceptible and tolerant to moisture stress, under natural water stress or potassium iodide-induced senescence of leaves und stem. The ear: stem ratio had significant correlation with grain yield, harvest index, single grain weight and grain-growth rate. Tillers had perceptible influence on association between the ratio and yield components. Path analysis, however, revealed that the correlation between the ratio and other traits was the indirect effect of grain weight. Ear: stem ratio was not as efficient as harvest index in differentiating susceptible and tolerant genotypes.